2016
DOI: 10.1007/s00702-016-1608-4
|View full text |Cite
|
Sign up to set email alerts
|

Low digit ratio (2D:4D) in male suicide victims

Abstract: Although women attempt suicides equally or more often than men do, men are more likely to die of suicide than women (sex paradox of suicidal behavior). Furthermore, the male traits of aggression and impulsivity predict suicide completion. Here, we studied the second-to-fourth-finger length ratio (2D:4D), a proxy for prenatal androgen exposure, in 46 suicide corpses and 25 non-suicide corpses. We report significantly lower 2D:4D in male suicide corpses than non-suicide corpses (p = .030, partial η 2 = .147). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
3
20
0
1
Order By: Relevance
“…Interestingly, the importance of the prenatal period was suggested by the association of restricted fetal growth with SB in adulthood [52]. Molecular evidence for prenatal effects in SB is scarce, but recent observation report about a low digit ratio (2D:4D) in male suicide victims, a trait which is a proxy for the prenatal exposure to androgens [53]. While the androgen receptor ( AR ) gene was not directly observed among our CNVs per se , AR has “guilt-by-association” in the PPI network presented here due to its central connectivity to the IGF1R , NDE1 , RB1 and AMH genes therein (if inserted into Fig F in S1 File; not shown), which is of interest to consider for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the importance of the prenatal period was suggested by the association of restricted fetal growth with SB in adulthood [52]. Molecular evidence for prenatal effects in SB is scarce, but recent observation report about a low digit ratio (2D:4D) in male suicide victims, a trait which is a proxy for the prenatal exposure to androgens [53]. While the androgen receptor ( AR ) gene was not directly observed among our CNVs per se , AR has “guilt-by-association” in the PPI network presented here due to its central connectivity to the IGF1R , NDE1 , RB1 and AMH genes therein (if inserted into Fig F in S1 File; not shown), which is of interest to consider for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower (prenatally more androgenized) 2D:4D has been reported in individuals with poorer health (Rapoza 2017 ), prostate cancer (Mendes et al 2016 ), primary brain tumors (Bunevicius et al 2016 ), alcohol dependence (Kornhuber et al 2011 ; Han et al 2016 ; Lenz et al 2017 ), anorexia nervosa in females (Quinton et al 2011 ), Alzheimer’s disease in females (Vladeanu et al 2014 ), and aggression-related injuries (Joyce et al 2013 ; O’Briain et al 2017 ). In addition, we recently provided the initial evidence for lower 2D:4D values in males who had died from suicide in comparison to males with other causes of death (Lenz et al 2016 ). Higher (prenatally more estrogenized) 2D:4D has also been associated with lethal diseases such as breast cancer (Muller et al 2012 ; Hong et al 2014 ), cervical dysplasia (Brabin et al 2008 ), oral squamous cell carcinoma in males (Nicolás Hopp and Jorge 2011 ), gastric cancer (Nicolás Hopp et al 2013 ), disordered eating in males (Smith et al 2010 ), Alzheimer’s disease in males (Vladeanu et al 2014 ), coronary heart disease (Lu et al 2015 ), and myocardial infarction (Kyriakidis et al 2010 ).…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, we used a hypothesis-free approach to further explore associations with specific causes of death, as defined by WHO. Many studies have shown sex-dependent relationships between 2D:4D and illness with stronger or exclusively significant associations in males, suggesting that prenatal sex hormone priming might be more relevant to lifetime health status in males in comparison to females (Martin et al 1999 ; Bailey and Hurd 2005 ; Martel et al 2008 ; Collinson et al 2010 ; Kyriakidis et al 2010 ; Kornhuber et al 2011 ; Nicolás Hopp et al 2013 ; Portnoy et al 2015 ; Lenz et al 2016 , 2017 ; Rapoza 2017 ) (but see also: Smedley et al 2014 ; O’Briain et al 2017 ). Thus, we analyzed sex-specifically whether normalized 2D:4D correlated with normalized life expectancy, suicide rates, and death rates from other causes across nations.…”
Section: Introductionmentioning
confidence: 99%
“…Values are presented as M ± SE. RMSSD = root mean square of successive differences died by suicide compared to men who had died by other means, while no statistically significant effects were observed for women (Lenz et al, 2016). However, another study did not identify an association between R2D4D and depressive symptoms (Austin, Manning, McInroy, & Mathews, 2002), while an additional study observed a positive association between R2D4D and depressive symptoms in women, but not in men (Smedley, McKain, & McKain, 2014).…”
Section: Lower 2d4d and Affectmentioning
confidence: 94%